SOCIAL DETERMINANTS OF COPING AMONG FILIPINO CULTURAL EDUCATORS IN THE TIME OF THE COVID-19 PANDEMIC - Rowalt Alibudbud; Richard Philip Gonzalo (Universitas PGRI Madiun, 2022)
The COVID-19 Pandemic has pushed the crisis to become part of the human condition. Improving coping capacities is crucial to sustaining a group's societal function. In the Philippines, generic policies that support educators were enacted by the government. However, programs that provide support to cultural educators as a distinct group are yet to be introduced. This study involved 200 Filipino cultural educators. Utilizing a cross-sectional methodology, it revealed that being female and identifying as female were negatively and positively associated with coping, respectively. Whether on a regular or contract basis, employment in cultural occupations was found to have a significant positive association with coping. Adequacy of financial support also mattered to cultural workers but receiving support at the town level negatively affected coping. These findings suggest considering personal and contextual factors to improve the coping capacity of cultural workers